Long QT interval revealing severe hypcalcemic dilated cardiomypathy : A case report - ZOUZOU, Hanane (Clinical Medicine And Health Research Journal, 2024)
Hypcalcemia is a rare cause of dilated cardiomyopathy, but should be suspected in the presence of an obvious long QT interval on the surface ECG; we report a case of 46 years-old-woman, with surgical history of thyroidectomy 6 years ago, admited in our cardiology departement for mangement of congestive heart failure secondary to dilated cardiomyopathy, her surface ECG showed sinus rhythm with long QT interval, his blood tests showed severe hypocalcemia and low serum concentration of parathyroid hormone (PTH), cardiac magnetic resonance imaging was in favor of non ischemic dilated cardiomyopathy. Concomitant with conventionel heart failure treatement, our patient had received parenteral calcium supplementation, vitamin D, levothyrox; after four weeks, heart failure symptomes were relieved, the intervalle QT has shortened, but persistant severe left ventricular systolic dysfuction. Hypoparathyroidism is frequent after thyroidectomy, and could be responsible of severe hypocalcemia which in turn may induce irreversible dilated cardiomyopathy.